2023
DOI: 10.3389/fonc.2023.1170336
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs and regulated cell death in tumor cells

Abstract: Regulated Cell Death (RCD) is a mode of cell death that occurs through drug or genetic intervention. The regulation of RCDs is one of the significant reasons for the long survival time of tumor cells and poor prognosis of patients. Long non-coding RNAs (lncRNAs) which are involved in the regulation of tumor biological processes, including RCDs occurring on tumor cells, are closely related to tumor progression. In this review, we describe the mechanisms of eight different RCDs which contain apoptosis, necroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 201 publications
(227 reference statements)
0
1
0
Order By: Relevance
“…Homologous lncRNAs can play different roles in different tumors. For example, LncRNA NEAT1 regulates pyroptosis in glioma cells and colorectal cancer cells by targeting miR-296-5p or miR-448; while its high expression promotes ferroptosis in non-small cell lung cancer 30 . Studies on the relationship between lncRNA and cuproptosis have been reported in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous lncRNAs can play different roles in different tumors. For example, LncRNA NEAT1 regulates pyroptosis in glioma cells and colorectal cancer cells by targeting miR-296-5p or miR-448; while its high expression promotes ferroptosis in non-small cell lung cancer 30 . Studies on the relationship between lncRNA and cuproptosis have been reported in various diseases.…”
Section: Discussionmentioning
confidence: 99%